EFL Pre-Service Teachers’ Coping Strategies Of Reducing Anxiety In Teaching - Safei, Nur Hasanah; Serliana, Serliana; Halim, Abdul (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2025)
This study investigates the coping strategies employed by EFL pre-service teachers to reduce teaching anxiety during their practicum at an Islamic institute in Southeast Sulawesi. The research is essential to address the psychological barriers that often compromise classroom engagement and teacher efficacy. It differentiates itself from previous research by focusing specifically on the unique field practice context in Southeast Sulawesi using Lazarus and Folkman’s transactional model. Adopting a qualitative case study design, the study involved five pre-service teachers selected via purposive sampling. Research instruments included a screening questionnaire and semi-structured interviews using pre-determined questions to collect in-depth qualitative data. The results reveal that participants utilized both problem-focused strategies (planful problem solving and seeking social support) and emotion-focused approaches (self-controlling, distancing, and positive reappraisal). Problem-focused methods were found to be more frequent as they directly resolved immediate classroom challenges and preparation needs. These findings conclude that proactive coping, supported by emotional regulation, effectively manages teaching pressure. The study implies the necessity of integrating formal coping-based training into teacher education programs to better prepare future teachers for the psychological demands of the classroom and improve their overall teaching performance.